(untitled) - Thesen, Sharon (Ontario, Canada, 1999)
New and smoke includes selections from all six of her previous books (which only Aurora remains in print). All of the work is imbued with a space, meticulous rigor, creating lines of a clear, pale light, punctuated by bursts of intense, flowering, staining colour.
Keywords: Canadian literature,Canadian poetry; 20th century